ENHANCING ORGANIZATIONAL PERFORMANCE: EVALUATING PERFORMANCE APPRAISAL SYSTEMS IN SELECTED INSURANCE COMPANIES WITH FOCUS ON SALEM DISTRICT - Maheswari, V. Uma; D. Suthamathi (ShodhKosh: Journal of Visual and Performing Arts, 2024)
This comprehensive study examines the performance appraisal systems within selected insurance companies in the Salem District, aiming to evaluate their effectiveness and propose recommendations for improvement. The study employs a quantitative research design, utilizing surveys and possibly interviews to gather data from employees and managers within the selected companies. Through systematic sampling, a sample size of 102 participants is determined, ensuring a diverse representation of perspectives. The findings reveal high internal consistency reliability (Cronbach’s Alpha = 0.924) among the measured items, indicating strong reliability in the measurement instrument. Demographic analysis shows no significant association between performance appraisal and variables such as gender, age, area of working, monthly income, and experience, except for a borderline significance with experience. However, significant differences are observed in work performance metrics based on gender and age, highlighting potential disparities in quality of work, quantity of work, teamwork, and collaborative behavior. The study’s implications for theory and practice underscore the importance of considering demographic variables in performance appraisal systems. Recommendations for improving these systems include clarifying performance criteria, providing manager training, implementing 360-degree feedback mechanisms, and leveraging technology solutions. Overall, this study contributes to both academic knowledge and practical implications in the field of insurance companies, offering insights for policymakers, HR professionals, and insurance company executives to enhance organizational performance and employee satisfaction. The duration of the study spans four months, from December 2023 to March 2024.In conclusion, this study provides valuable insights into performance appraisal systems within the insurance sector, laying the foundation for future research and practice in the field.